Severe rectal complications after prostate brachytherapy. Issue 2 (February 2015) - Wallner, Kent; Sutlief, Stephen; Bergsagel, Carl; Merrick, Gregory S.
Abstract Purpose Some investigators have reported severe rectal complications after brachytherapy. Due to the low number of such events, their relationship to dosimetric parameters has not been well characterized. Methods and materials A total of 3126 patients were treated with low dose rate brachytherapy from 1998 through 2010. 2464 had implant alone, and 313 had implant preceded by 44–46 Gy supplemental external beam radiation (EBRT). Post-implant dosimetry was based on a CT scan obtained on the day of implant, generally within 30 min of the procedure. Every patient's record was reviewed for occurrence of rectal complications. Results Eight of 2464 patients (0.32%) treated with brachytherapy alone developed a radiation-related rectal fistula. Average prostatic and rectal dose parameters were moderately higher for fistula patients than for patients without a severe rectal complication. For instance, the average R100 was 1.2 ± 0.75 cc for fistula patients, versus 0.37 ± 0.88 cc for non-fistula patients. However, the fistula patients' values were well within the range of values for patients without a rectal complication. Four patients had some attempt at repair or reconstruction, but long-term functional outcomes were not favorable. Conclusions Rectal fistulas are a very uncommon potential complication of prostate brachytherapy, which can occur even in the setting of acceptable day 0 rectal doses. Their occurrence is not easily explained by standard dosimetric or clinical factors.